Genetic improvement of the BR 5028 - São Francisco corn variety at the Brazilian Northeast region - Wilson Lemos de Carvalho, Hélio; Xavier dos Santos, Manoel; de Lourdes da Silva Leal, Maria; Antônio Patto Pacheco, Cleso (Pesquisa Agropecuaria Brasileira, 1998)
Four selection cycles were carried out among and within progenies of half-sibs on the population of BR 5028 - São Francisco corn variety in 1991, 1992, 1994 and 1995 at Neópolis and Lagarto, SE, Brazil. The work aimed at obtaining a higher productive and better adapted variety for the region environment. The progenies were evaluated on a 14 x 14 latice design, with two replications. Recombination of the outstanding progenies was processed within the same year crop in order to get one cycle per year. The values of the genetics parameters decreased with the proceedings of the selection cycles; such reduction was more evident at VIII and IX cycles when progenies evaluation started to be conducted at two sites, having weaker influence of the progenies x environment interaction. The high magnitudes of the genetic parameters associated with the high productivity means of progenies and with the expected averaged gain from the selection among and whithin progenies per selection cycle (29,8%) show the high potential of the variety to respond to selection, which will permit to attain a higher production and a material better adapted to the regional environment.